2021
DOI: 10.1158/1078-0432.ccr-20-3201
|View full text |Cite
|
Sign up to set email alerts
|

CamGFR v2: A New Model for Estimating the Glomerular Filtration Rate from Standardized or Non-standardized Creatinine in Patients with Cancer

Abstract: Purpose: Management of patients with cancer, specifically carboplatin dosing, requires accurate knowledge of glomerular filtration rate (GFR). Direct measurement of GFR is resource limited. Available models for estimated GFR (eGFR) are optimized for patients without cancer and either isotope dilution mass spectrometry (IDMS)- or non-IDMS–standardized creatinine measurements. We present an eGFR model for patients with cancer compatible with both creatinine measurement methods. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…eGFRcr was determined from the 1976 CG, 4 2006 MDRD, 5 2009 CKD-EPI, 6 and 2020 CamGFRv2 equations. 9 eGFRcys and eGFRcr-cys were determined from the 2012 CKD-EPI equation 15 (Supplementary Table S1). eGFR was indexed for body surface area and expressed as ml/min per 1.73 m 2 .…”
Section: Data Collection Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…eGFRcr was determined from the 1976 CG, 4 2006 MDRD, 5 2009 CKD-EPI, 6 and 2020 CamGFRv2 equations. 9 eGFRcys and eGFRcr-cys were determined from the 2012 CKD-EPI equation 15 (Supplementary Table S1). eGFR was indexed for body surface area and expressed as ml/min per 1.73 m 2 .…”
Section: Data Collection Proceduresmentioning
confidence: 99%
“…Recent studies in patients with solid tumors have shown a potential for error in chemotherapy prescriptions using the CG equation. [7][8][9] Estimated GFR (eGFR) based on Scr (eGFRcr) using the CKD-EPI equation is recommended as the "first test" for GFR evaluation for routine clinical practice in adults. 10 Patients with cancer were not well represented in the studies in which newer eGFR equations were derived, and for several reasons, the CKD-EPI equation may be less accurate in patients with cancer than in the general population.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we sought to test a novel equation (CamGFR v2) that was developed and validated recently on a large cohort of patients with cancer. 9 To our knowledge, this equation has not been previously tested in a cohort consisting of only patients with gynaecological malignancies. Using Lin's CCC, we found that among all equations evaluated, the CamGFR v2 and CG-AdBW provided the best agreement with nmGFR.…”
Section: Discussionmentioning
confidence: 99%
“…Only two have been validated in patients with cancer, the Wright formulae and the CamGFR v2 formula. 8,9 Previously, eGFR for patients with gynaecological malignancies was commonly derived using the Jelliffe equation. Subsequently, many laboratories recalibrated their creatinine assays using an isotope dilution mass spectroscopy (IDMS)-traceable reference method.…”
Section: Introductionmentioning
confidence: 99%